Housing tenure in Ireland - Somerville, R. A. (Economic & Social Studies, 2007)
This paper investigates the sources of the extremely high level of owner occupation in Ireland. After using census data to explore the evolution of this phenomenon, the paper makes a cross-country comparison of owner occupation within the EU-15. Explanations are found for the high level of owner occupation that go beyond fiscal privilege to include wider microeconomic factors, as well as historical factors. Within the EU-15, the Irish housing stock is exceptional not just in the high incidence of owner occupation, but also in the small number of dwellings relative to population.
Keywords: Residential property; Housing tenure; Ireland; Owner occupation